Preserving Javanese Language and Culture in The Digital Age : Challenge and Future Prospects - Anistya Ori, Salindri; Susianti, Hartanti Woro (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2023)
Javanese holds a central place in the rich tapestry of Indonesian culture, and its significance extends far beyond mere linguistic communication. Its historical roots, role in art and tradition, importance in shaping regional and national identities, and contribution to the nation's literary heritage make it a language of immense significance in Indonesian culture, which needs to be preserved and passed down to future generations. Javanese language revitalization efforts by utilizing digital technology, such as websites, applications, and social media, have become effective as they are easily accessible and engaging. It empowers indigenous communities to take control of their own preservation efforts while connecting them with a global network of supporters and resources. This literature study aims to describe Javanese language preservation in the digital age. Data is obtained from various sources of journals, books, documentation, and the internet. The result of this study is that digital learning serves as a dynamic and inclusive tool to preserve the Javanese language and culture, making it more accessible, engaging, and customizable to the needs and preferences of a diverse and digitally connected audience. The digital age has opened up exciting opportunities to not only explore this rich heritage but also contribute to its preservation.